2013
DOI: 10.1093/alcalc/ags134
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Consumption and Mortality in Russia since 2000: Are there any Changes Following the Alcohol Policy Changes Starting in 2006?

Abstract: Alcohol is a strong contributor to premature deaths in Russia, with both the volume and the pattern of consumption being detrimental to health. The regulations introduced since 2006 seem to have positive effects on both drinking behavior and health outcomes. However, there is an urgent need for further alcohol-control strategies to reduce alcohol-related harm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
79
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(86 citation statements)
references
References 44 publications
5
79
1
1
Order By: Relevance
“…Another indicator of alcohol abuse, namely mortality from accidental poisonings by alcohol, also illustrates the changes in Russian drinking pat- It is highly likely that a decline in alcohol consumption is largely responsible for the recent reduction in premature mortality. Previous studies demonstrated a close link between rapid changes in alcohol consumption and CVD mortality in Russia (Shkolnikov and Nemtsov 1997;Shkolnikov et al 2004b;Neufeld and Rehm 2013). Similar changes in CVD mortality were observed in Estonia in 1985-87 and in 1992-94.…”
Section: Explanations For the Observed Improvementsupporting
confidence: 63%
See 1 more Smart Citation
“…Another indicator of alcohol abuse, namely mortality from accidental poisonings by alcohol, also illustrates the changes in Russian drinking pat- It is highly likely that a decline in alcohol consumption is largely responsible for the recent reduction in premature mortality. Previous studies demonstrated a close link between rapid changes in alcohol consumption and CVD mortality in Russia (Shkolnikov and Nemtsov 1997;Shkolnikov et al 2004b;Neufeld and Rehm 2013). Similar changes in CVD mortality were observed in Estonia in 1985-87 and in 1992-94.…”
Section: Explanations For the Observed Improvementsupporting
confidence: 63%
“…The recent mortality reduction does not appear to be an exception. According to Neufeld and Rehm (2013), the real alcohol consumption (of pure ethanol) including its unrecorded part has been decreasing in Russia, with a clear acceleration of the decrease in 2006-07. The decline in consumption of spirits in these years has been even steeper.…”
Section: Explanations For the Observed Improvementmentioning
confidence: 99%
“…These aggregate-level findings are comparable to previous individual-level estimates for males (37.0%), but exceed substantially estimates for females (9.2%) [23]. Relatively high estimates of AAF for women, where heavy drinking is restricted to a relatively small proportion of the population, gives rise to the suspicion of possible measurement error and may imply that the alcohol effect for women is overestimated.…”
Section: Discussionsupporting
confidence: 72%
“…The law contained regulations aimed at controlling the volume and quality of alcohol products and requiring the registration of alcohol production and distribution facilities. A coincidence in the TB mortality and alcohol sales trends between 2004 and 2010 allows us to hypothesize that the reduction in the TB mortality rate during the most recent years might be attributed to the implementation of the alcohol policy reforms, which increased government control over the alcohol market [23]. A fairly close aggregate-level match between alcohol sales and TB mortality rate during the Gorbachev's anti-alcohol campaigns and during the last years may be use as evidence for the hypothesis suggesting that a restrictive alcohol policy can be considered as an effective measure of TB mortality prevention.…”
Section: Discussionmentioning
confidence: 99%
“…They make an exception only for 2006-2007, as do other authors [Neufeld, Rehm 2013], who, however, noted an important fact: the new alcohol policy went into effect in 2000. Pridemore and co-authors [Pridemore et al 2014] [Shkolnikov et al, 2014] to the conclusion that the greatest contribution to the increase in life expectancy was made by the reduction in adult mortality from diseases of the circulatory system and external causes most closely associated with alcohol consumption.…”
Section: Causes Of the Reduction Of Mortality After 2003mentioning
confidence: 84%